2022
DOI: 10.54183/jssr.v2i4.82
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Entrepreneurial Leadership in Decent Work and Economic Growth: A Sustainable Development of Textile Industry of Pakistan

Abstract: The following research paper aimed to examine the role of entrepreneurial leadership in sustainable development goals (SDGs) particularly Goal 8 focusing decent work and economic growth. The study has been conducted under the context of textile industry of Pakistan. The findings showed a literature gap in the area of entrepreneurial leadership and SDG8. In recent years, demand of entrepreneurial leadership has increased because such leaders demonstrate risk taking, empathetic, strategic and visionary behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…It provides new ideas for cross-level research on DW based on the results of this study. Previous studies have confirmed the impact of positive leadership on DW, such as entrepreneurial leadership (Shehri et al, 2022), and negative leadership styles, such as toxic leadership (Casqueira, 2019). However, leaders' leadership is diverse and complex.…”
Section: Theoretical Contributionsmentioning
confidence: 83%
“…It provides new ideas for cross-level research on DW based on the results of this study. Previous studies have confirmed the impact of positive leadership on DW, such as entrepreneurial leadership (Shehri et al, 2022), and negative leadership styles, such as toxic leadership (Casqueira, 2019). However, leaders' leadership is diverse and complex.…”
Section: Theoretical Contributionsmentioning
confidence: 83%